2015
DOI: 10.1111/1365-2435.12509
|View full text |Cite
|
Sign up to set email alerts
|

Visual and odour cues: plant responses to pollination and herbivory affect the behaviour of flower visitors

Abstract: 1. Plants evolved strategies to attract pollinators that are essential for reproduction. However, plant defence against herbivores may trade off with pollinator attraction. 2. Here, we investigated the role of inducible plant secondary metabolites in such a trade-off. Our objective was to reveal the mechanisms underlying the effects of induced plant responses to pollination and herbivory. We assessed how responses of plants to pollination and insect herbivory affect the behaviour of flower visitors. Subsequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
99
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 68 publications
(106 citation statements)
references
References 47 publications
0
99
0
Order By: Relevance
“…obs. ), supporting the hypothesis that plants redirect resources from leaves to the inflorescences upon attack, and activate resistance traits in flower tissues (Lucas‐Barbosa et al ., , , ; Pashalidou et al ., ; Lucas‐Barbosa, ), in accordance with the optimal defense theory (Cates & Rhoades, ). We speculate that plant responses to egg deposition on leaves, which typically induces SA, may have inhibited an early induction of JA in the inflorescence by the caterpillars when recorded at day 8, that is, 3 d after the caterpillars had hatched from the eggs, providing also a possible explanation of why higher phytohormonal concentrations were quantified at day 12 than at day 8 (Bruessow et al ., ; Hilker & Fatouros, ).…”
Section: Discussionmentioning
confidence: 99%
“…obs. ), supporting the hypothesis that plants redirect resources from leaves to the inflorescences upon attack, and activate resistance traits in flower tissues (Lucas‐Barbosa et al ., , , ; Pashalidou et al ., ; Lucas‐Barbosa, ), in accordance with the optimal defense theory (Cates & Rhoades, ). We speculate that plant responses to egg deposition on leaves, which typically induces SA, may have inhibited an early induction of JA in the inflorescence by the caterpillars when recorded at day 8, that is, 3 d after the caterpillars had hatched from the eggs, providing also a possible explanation of why higher phytohormonal concentrations were quantified at day 12 than at day 8 (Bruessow et al ., ; Hilker & Fatouros, ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have identified flower traits that are affected by herbivory (Bruinsma et al., ; Hoffmeister, Wittköpper, & Junker, ; Lucas‐Barbosa et al., ; Pareja et al., ), and some flower traits might change in response to herbivory because they share biosynthetic pathways or resources with defensive traits (Fineblum & Rausher, ; Herms & Mattson, ; Johnson, Campbell, & Barrett, ). Subsequently, herbivore‐induced plants have been found to negatively affect pollinator attraction and visitation (Barber, Adler, Theis, Hazzard, & Kiers, ; Liao, Gituru, Guo, & Wang, ; Schiestl, Kirk, Bigler, Cozzolino, & Desurmont, ), but there are also reports of neutral (Ivey & Carr, ; Lucas‐Barbosa et al., ) or positive effects on pollinator attraction (Barber, Adler, & Bernardo, ; Poveda, Steffan‐Dewenter, Scheu, & Tscharntke, ). Only few studies addressed the effect of plant responses to herbivory on antagonist flower visitors, such as florivores and seed predators.…”
Section: Introductionmentioning
confidence: 99%
“…To fine‐tune defences against the diversity of herbivores, we expect that plants can recognize and respond to each attacker specifically (Agrawal, ; Travers‐Martin & Müller, ; Uesugi, Poelman, & Kessler, ) and plant responses can vary based on pattern of damage (Mithöfer, Wanner, & Boland, ) and compounds released by herbivores during feeding (Howe & Jander, ; Wu & Baldwin, ). Herbivores with similar feeding modes (Bidart‐Bouzat & Kliebenstein, ; Erb, Meldau, & Howe, ; Howe & Jander, ; McCormick, Unsicker, & Gershenzon, ) or that feed on the same plant organs (Farré‐Armengol, Filella, Llusia, Primante, & Peñuelas, ; Johnson, Erb, & Hartley, ; Lucas‐Barbosa et al., ) induce more similar plant responses than herbivores that differ in feeding guild or feeding site. For example, chewing insects primarily induce the jasmonic acid (JA)‐dependent defence pathway, whereas sap‐feeding insects may suppress JA and/or induce the salicylic acid (SA)‐dependent defence pathway (De Vos et al., ; Heidel & Baldwin, ; Rodriguez‐Saona, Crafts‐Brandner, & Cañas, ; Rowen & Kaplan, ; Turlings et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Such synecological approaches can be complemented with autecological studies addressing the specific traits that influence Challenges in insect-plant interactions 323 long-lasting, community-wide effects. Thus, although studies of plant-pollinator interactions and studies of plant-herbivore interactions have often been carried out independently, more integrative studies combining these interactions and their consequences are now emerging (Kessler & Halitschke, 2009;Lucas-Barbosa et al, 2016). The latter may occur in different plant tissues, such as seeds (Hernandez-Cumplido et al, 2016) or roots (Rasmann et al, 2005), or in different tissues that may influence or interact with each other (Soler et al, 2013).…”
Section: Challenges In Insect-plant Interactions 321mentioning
confidence: 99%
“…Future challenges include the following: 1 To integrate species interactions and related traits in multitrophic-multitrait systems at the scale of the entire community. Integrating studies of plant defence and plant reproduction will help to understand the factors that influence interactions of plants with various interactants (Lucas- Barbosa et al, 2016;Chr etien et al, 2018). Ideally, such approach should map the various effectors and elicitors from each partner acting across the networks.…”
Section: Future Promises and Challengesmentioning
confidence: 99%